Skin Pathology Laboratory of the Department of Dermatology of Hospital de Santa Maria. Twelve Years of Activity (2008-2019) - Part I: Skin Tumors - Aguado Lobo, Marta (2020)
Introduction: The Skin Pathology Laboratory of the Department of Dermatology of Hospital de Santa Maria, Lisbon, has been operating continuously since its creation. Material and Methods: A retrospective study was conducted through the analysis of the histological exams of the tumoral skin pathology of the Laboratory between January 2008 and December 2019. Results: In the period 2008-2019 the Skin Pathology Laboratory performed 60 741 histological exams, of which 80% were tumoral lesions. Of these, malignant tumors represented about one third of the sample, essentially constituted by basal cell carcinomas (53%), squamous cell carcinomas (23%) and melanomas (8%). Other malignant tumors were lymphomas (3%), Kaposi's sarcoma (1%) and skin disorders due to extracutaneous malignancies (2%). The group of benign neoplasms (68% of the total number of tumors) included melanocytic nevi (50%), seborrheic keratosis (16%) and cysts (6%). Conclusion: Comparing with former casuistic studies, a steady and regular increase in the general activity of the Laboratory of Cutaneous Histopathology at the Dermatology Service of Hospital de Santa Maria has been observed in the past 12 years. This has been reflected in an increase in the number of diagnoses of malignant skin tumors. We highlight the value of histological examination as a central component in the diagnosis and subsequent treatment of neoplastic skin conditions.